UTILIZATION OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY IN THE DIGITIZATION OF MSMES IN CILEGON CITY - Adha, Suhroji; Mukhlasin, Mukhlasin; Yulieti P., Ratu Miki; Setyarandini, Venia; Asaroh, Yunia; Fauzul, Ahmad; Rizal, Rizal (LPPM Univ. Ibn Khaldun Bogor, 2025)
Digitalization has become a primary necessity for Micro, Small, and Medium Enterprises (MSMEs) to thrive and grow in the digital era. In the city of Cilegon, many MSMEs still rely on traditional methods, which causes them to lag slightly behind in the digital market. Through this community service activity, training and assistance were provided on utilizing Artificial Intelligence (AI) technology in various business aspects, such as digital marketing, financial management, and product branding. The solution offered was AI education tailored to the specific needs of business owners. The results showed an increase in participants' knowledge and skills in using technology to support operations and enhance the competitiveness of local products. In conclusion, the use of AI contributes positively to encouraging the digital transformation of MSMEs, improving business efficiency, and sustainably expanding market reach.